Langkah Kepala Sekolah Dalam Pengambilan Keputusan - Reni Arneti; Nasrul; Nurhizrah Gistituati; Hadiyanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This study aims to learn how SMP Negeri 5 Bukittinggi's school principal uses their leadership style to make decisions about disciplinary violations. This exploration is subjective examination, as a contextual investigation. In this exploration, the school head, teachers and understudies were the asset people. In this examination, information was gathered through interview strategies, perception and documentation. The strategy utilized is source triangulation. The discoveries from the examination express that 1) The school head's dynamic cycle depends on recognizing issues in regards to infringement of educator and understudy discipline, where the outcomes show that the chief carries out a technique by gathering the infringement into gentle, moderate to serious classes and afterward deciding suitable authorizations. will be given. Then the following methodology, 2) In the dynamic cycle in view of the reason for the event, where the school chief glances at what made the infringement happen. Lastly 3) The dynamic interaction depends on the effect on understudies and educators, where the procedure carried out by the school chief is to lay out correspondence and socialization with the goal that instructors and understudies are more focused